2023
DOI: 10.1109/tcst.2022.3187916
|View full text |Cite
|
Sign up to set email alerts
|

Attitude Reconstruction of a Spacecraft From Temperature Measurements in Solar Eclipse Analysis and Observer Design for a Not Globally Observable Non-Linear System

Abstract: This article proposes a method that uses only a single temperature measurement and angular velocity measurements to estimate the attitude of a spacecraft under the influence of solely infrared irradiation. The system governing the dynamics is highly non-linear with its attitude being defined in the quaternion space. The resulting observability mapping is used to transform the system into a canonical observability form. However, this mapping is not bijective, and a method to find the arising local inverses is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This approach considers the existing correlation between thermal data and the orientation of the spacecraft. Other studies, such as [7], have also explored the use of thermal data to determine the attitude of satellites. Furthermore, Gadalla Mohamed et al [3] demonstrated that the temperature difference between surfaces of a moving spacecraft can be significantly affected by its rotation, enabling the determination of the spacecraft's rotation rate.…”
Section: Introductionmentioning
confidence: 99%
“…This approach considers the existing correlation between thermal data and the orientation of the spacecraft. Other studies, such as [7], have also explored the use of thermal data to determine the attitude of satellites. Furthermore, Gadalla Mohamed et al [3] demonstrated that the temperature difference between surfaces of a moving spacecraft can be significantly affected by its rotation, enabling the determination of the spacecraft's rotation rate.…”
Section: Introductionmentioning
confidence: 99%